Activated grass carp STAT6 up-regulates the transcriptional level and expression of CCL20 and Bcl-xl. Issue 80 (September 2018) - Ran, Xiaoqin; Liu, Changxin; Weng, Panwei; Xu, Xiaowen; Lin, Gang; Qi, Guoqin; Yu, Ningli; Xu, Kang; Wu, Zhen; Hu, Chengyu
Abstract: In mammals, signal transducer and activator of transcription 6 (STAT6) is a broad-spectrum transcriptional regulator involved in cellular immune responses and apoptosis by regulating the immune-related genes and various functional genes. The structure, expression and tyrosine-based phosphorylation of STAT6 are conserved from fish to mammal. However, except the sporadic reports from zebra fish, the function of fish STAT6 has not been well reported. Here, we cloned and characterized the full length cDNA sequence of grass carp ( Ctenopharyngodon idella ) STAT6 ( CiSTAT6 ). Meanwhile, the activation mechanism and the potential function of CiSTAT6 were studied. The full length cDNA of CiSTAT6 is 2747 bp with an ORF of 2313 bp encoding a polypeptide of 770 amino acids. Phylogenetic tree analysis revealed that CiSTAT6 shares the maximum homology with Cyprinus carpio STAT6. CiSTAT6 was significantly up-regulated and interacted with each other to form the homodimer after treatment with poly I:C. The transfected CiSTAT6 in fish cell lines can activate the promoter activities of CCL20 and Bcl-xl and increase their mRNA levels. In addition, we also found that CiSTAT6 can increase cell viability and inhibit cell apoptosis. Taken together, grass carp STAT6 plays an important part in innate immunity and anti-apoptosis. Highlights: Grass carp STAT6 responds to poly I:C. Grass carp STAT6 can form the homodimer under poly I:C processing. Grass carp STAT6 up-regulates the transcriptional levels and expressions of CCL20 and Bcl-xl. Overexpression of grass carp STAT6 enhances cell activity and inhibits apoptosis.